Electrical thermal heating and piezoresistive characteristics of hybrid CuO–woven carbon fiber/vinyl ester composite laminates. (June 2016) - Kong, Kyungil; Cheedarala, Ravi Kumar; Kim, Myungsoo; Roh, Hyung-Doh; Park, Young-Bin; Park, Hyung Wook
Abstract: The electric heating and piezoresistive characteristics of CuO–woven carbon fiber (CuO–WCF) composite laminates were experimentally evaluated. Hybrid CuO–WCF composites were fabricated via a two-step seed-mediated hydrothermal method. The interlaminar interface between two plies of hybrid CuO–WCF/vinyl ester composite laminae was influenced by interlocked fiber–fiber cross-linking structures with CuO NRs and acted as electric heating and resistance elements. The contribution of CuO NRs (10–110 mM) to the interlaminar interface was determined by measuring the temperature profile, in order to investigate the electrical resistive heating behavior. At higher concentration of CuO NRs growth in the interlaminar region applied by 3 A, the average temperature reached to 83.55 °C at the interface area 50 × 50 mm 2 and the heating efficiency was 0.133 W/°C owing to radiation and convection given by 10.5 W (3 A, 3.5 V). To investigate the piezoresistive response, the through-thickness gauge factor was observed at 0.312 during Joule heating applied by 2 A, compared with 0.639 at an ambient air temperature for CuO 110 mM concentration. The morphology and crystallinity of CuO NRs were investigated using scanning electron microscopy and X-ray diffraction analyses, respectively. The temperature dependence of hybrid CuO–WCF composite laminates' storage moduli were analyzed using a dynamic mechanical analyzer. These characterizations showed that the interlaminar interface, combined with the high specific surface area of CuO NRs, provided the electron traps for electrical conduction around multiple WCF junctions and adjacent cross-linked laminae.